Utilization of Rice Husk Waste Into Rice Husk Charcoal as an Environmentally Friendly Planting Media In Pimping Village - Putra, Marlan Usmani; Hariyati, Tati; S, Sabarudin; R, Risnafaty; Imelda, Dewi Qomariah; Bagus, Qodrat (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
This community service activity aims to provide understanding and training to junior high school students in Pimping Village about the utilization of rice husk waste into rice husk charcoal as a mixture of planting media. Rice husks, which have been considered waste, actually have great potential if processed by pyrolysis to produce rice husk charcoal. Rice husk charcoal has good physical properties, such as high aeration capacity, water retention capacity, and nutrient content that can improve the quality of planting media. The method used is education and training for junior high school students at TPU 3 with a total of 49 participants. The results of the activity increased the understanding of junior high school students about the processing of rice husk waste, as well as the benefits of utilizing rice husk charcoal to support sustainable agriculture. With socialization and training, it can increase the knowledge of participants, especially junior high school students, TPU can utilize waste optimally, thereby reducing the remaining waste from milling in the form of discarded rice husks which were previously of little value by processing the husk into rice husk charcoal which has economic value and can even be used as a more effective and environmentally friendly planting medium.